Types of Honorific Address in Male Communication at Universitas Pamulang - Egilistiani, Rahmita; Ratnaningtyas, Theresia Ningrum; Pratama, M.Renaldi Putra (Journal Corner of Education, Linguistics, and Literature, 2025)
Honorifics are an essential aspect of sociolinguistic studies because they represent how language reflects respect, hierarchy, and cultural values within a community. This study focuses specifically on identifying the types of honorific addresses employed in male communication within the English Literature Department of Universitas Pamulang. By limiting the scope to the categorization of address terms, the research aimed to contribute a detailed understanding of how men employ different honorifics in both formal and informal settings. A qualitative descriptive method was applied to explore these linguistic patterns. The participants consisted of 58 male respondents, including students, lecturers, and staff, who were selected purposively to represent a range of academic and social backgrounds. Data were collected through questionnaires, interviews, and direct observations, and were then analyzed thematically to identify recurring address terms. The findings reveal that male speakers at Universitas Pamulang utilize a variety of honorifics, such as Bang, Bro, Mas, Pak, Om, Kak, and Kang. These forms indicate a strong tendency to differentiate address terms based on social closeness, hierarchy, and cultural habit.